Picturing mind : paradox, indeterminacy and consciousness in art & poetry - Danvers, John (Consciousness, literature & the arts, 2006)
In this book the author takes an unusual multi-disciplinary approach to debates about contemporary art and poetry, ideas about the mind and its representations, and theories of knowledge and being. Arts practices are considered as enactments of mind and as transformative modes of consciousness. Ideas drawn from poetics, philosophy and consciousness studies are used to illuminate the conceptual and aesthetic frameworks of a diverse array of visual artists. Themes explored include: the interconnectedness of existence; art as a way of interrogating appearances; identity and otherness; art and the.